2013
DOI: 10.1111/jnc.12624
|View full text |Cite
|
Sign up to set email alerts
|

Activation of rhodopsin gene transcription in cultured retinal precursors of chicken embryo: role of Ca2+ signaling and hyperpolarization‐activated cation channels

Abstract: This study reports that the spontaneous 50-fold activation of rhodopsin gene transcription, observed in cultured retinal precursors from 13-day chicken embryo, relies on a Ca 2+-dependent mechanism. Activation of a transiently transfected rhodopsin promoter (luciferase reporter) in these cells was inhibited (60%) by cotransfection of a dominant-negative form of the cAMP-responsive element-binding protein. Both rho-dopsin promoter activity and rhodopsin mRNA accumulation were blocked by Ca 2+ /calmodulin-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Considering the various roles HCN channels play in the CNS, it is plausible that they may also play a role in retinal function if they exist in the retina. Indeed, it is well known that all four isoforms of HCN channels (i.e., HCN1-4) are distinctively expressed in various classes of neurons across the vertebrate retinas ( Moosmang et al, 2001 ; Müller et al, 2003 ; Ivanova and Müller, 2006 ; Cangiano et al, 2007 ; Barrow and Wu, 2009 ; Della Santina et al, 2010 , 2012 ; Bernard et al, 2014 ; Hellmer et al, 2016 ). Although HCN channels have not been well explored in the human retinas, it is worth noting that some patients who were prescribed ivabradine which is an HCN inhibitor to lower their heart rate reported visual disturbances, mostly phosphene-like phenomena ( Gargini et al, 1999 ; Borer et al, 2003 ; Mao et al, 2003 ; Camm, 2006 ; Cangiano et al, 2007 ; Cervetto et al, 2007 ; Della Santina et al, 2010 ), indirectly suggesting the considerable expression of HCN channels in the human visual pathway.…”
Section: Known Function and Localization Of Hcn Channels In The Retinamentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the various roles HCN channels play in the CNS, it is plausible that they may also play a role in retinal function if they exist in the retina. Indeed, it is well known that all four isoforms of HCN channels (i.e., HCN1-4) are distinctively expressed in various classes of neurons across the vertebrate retinas ( Moosmang et al, 2001 ; Müller et al, 2003 ; Ivanova and Müller, 2006 ; Cangiano et al, 2007 ; Barrow and Wu, 2009 ; Della Santina et al, 2010 , 2012 ; Bernard et al, 2014 ; Hellmer et al, 2016 ). Although HCN channels have not been well explored in the human retinas, it is worth noting that some patients who were prescribed ivabradine which is an HCN inhibitor to lower their heart rate reported visual disturbances, mostly phosphene-like phenomena ( Gargini et al, 1999 ; Borer et al, 2003 ; Mao et al, 2003 ; Camm, 2006 ; Cangiano et al, 2007 ; Cervetto et al, 2007 ; Della Santina et al, 2010 ), indirectly suggesting the considerable expression of HCN channels in the human visual pathway.…”
Section: Known Function and Localization Of Hcn Channels In The Retinamentioning
confidence: 99%
“…For example, in rodents, HCN1 isoform was also found throughout the whole retinal layers such as the nerve fiber layer (NFL), ganglion cell layer (GCL), inner plexiform layer (IPL), outer plexiform layer (OPL), and outer nuclear layer (ONL) ( Table 1 ). Although rabbits showed the rodent-like distribution of HCN1 channel in the GCL, IPL, INL, and ONL ( Kim et al, 2003 ), in chicken embryo retina, HCN1 isoform was only observed in IPL and OPL ( Bernard et al, 2014 ). On the other hand, HCN1 isoform was expressed only in ONL and IPL of salamander ( Barrow and Wu, 2009 ) and macaque ( Puthussery et al, 2013 ) retinas, respectively.…”
Section: Known Function and Localization Of Hcn Channels In The Retinamentioning
confidence: 99%
“…The HCN channel family comprises 4 members, designated HCN1-4, which are permeable to Na + and K + (17). HCN channels activate T-type voltage-dependent Ca 2+ channels via membrane depolarization, which alters intracellular Ca 2+ concentrations (18). …”
Section: Introductionmentioning
confidence: 99%